Integrasi Islam dan Sains dalam Perspektif Pemikiran K.H. Ahmad Dahlan dan Implementasinya di Universitas Muhammadiyah Malang (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study aims to examine K.H. Ahmad Dahlan's thoughts on the integration of Islam and science and its application at Muhammadiyah University Malang. The background of this study is the challenge of modern Islamic education, where religious and general knowledge are often separated, while Ahmad Dahlan emphasizes the need for synergy between the two to shape a generation of Muslims who are faithful, knowledgeable, and moral. This study uses a qualitative approach with a literature review method, utilizing primary and secondary literature as well as UMM academic documents. Descriptive-analytical analysis was conducted to understand Ahmad Dahlan's philosophical foundations and to examine their implementation through the curriculum, AIK courses, and academic and non-academic activities. The results of the study show that Ahmad Dahlan's thinking forms a solid foundation for the integration of religious and general knowledge, while its implementation at UMM is reflected in the strengthening of Islamic values throughout the academic process. In conclusion, the integration of Islam and science at PTM shapes individuals who are balanced between faith, knowledge, and deeds, and serves as a model of Islamic education that is adaptive to the demands of modern times.